General Public Knowledge, Source of Knowledge and Practice towards Antibiotics in the State of Penang, Malaysia - Mahmoud Sa'di Al-Haddad (Archives of Global Professionals, 2012)
Objectives: This study aims to investigate the general publicknowledge, source of knowledge, and practice towardsantibiotics in the state of Penang Malaysia.Methods: A cross sectional study design using conveniencesampling technique was adopted in this study from May 2010until August 2010. A pre-validated questionnaire wasdeveloped and distributed to 700 participants in the state ofPenang, Malaysia. All data was analysed using SPSS version 16.A p-value of less than 0.05 was considered significant.Results: 85.6% of our respondents could correctly identifythat antibiotics are used for bacterial infections whereasalmost 58% believed that antibiotics are used for viralinfections. Physicians and pharmacists were the main sourcesof knowledge about antibiotics. While around 30% of ourrespondents rely on the internet, family members and friendsas their sources of information about antibiotics. Malpracticeregarding antibiotics use was found in a high proportion of ourrespondents where many use antibiotics without prescription,prescribe the leftover antibiotics to their friends and familymembers while others modify the antibiotics dose withoutreferring to healthcare professional and others stop theantibiotics course once they feel that their symptoms improve.Conclusion: Malpractice regarding antibiotics was found in agreat proportion of our respondents which might be due to theirrational prescription of antibiotics by healthcareprofessionals as well as due to the misleading sources ofknowledge about antibiotics. There is a need for a nationalawareness program to the public and healthcare professionalsabout antibiotics and about the approaches to improve thecurrent practice.